2011
DOI: 10.1097/aud.0b013e3181e8534c
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Plasticity and Speech Perception in Pre- and Postlingually Deaf Cochlear Implant Users

Abstract: The results suggest that cross-modal plasticity accounts for a significant amount of the variability observed in speech perception performance with a cochlear implant in individuals with prelingual onset of severe to profound hearing loss but not in individuals who acquire severe to profound hearing loss later in life. Furthermore, the results suggest that the influence of cross-modal plasticity on speech perception ability is more greatly influenced by when (pre- or postlingually) a person acquires a severe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
100
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 59 publications
21
100
2
1
Order By: Relevance
“…Specifically, crossmodal plasticity is only found in a correlational analysis (whereby the shorter the period of visual recovery, the higher the visual cortical responses to auditory stimulation; present study) and in multisensory conditions involving concurrent visual stimulation (Guerreiro et al, 2015). These results resemble those obtained in the domain of auditory restoration but after late-onset deafness: although crossmodal plasticity after cochlear implantation in deaf individuals is often reported (Doucet et al, 2006;Buckley and Tobey, 2011;Sandmann et al, 2012;Stropahl et al, 2015), a recent longitudinal study found that crossmodal visual responses within auditory areas decrease after auditory restoration, eventually reaching the level observed in normally hearing controls (Rouger et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…Specifically, crossmodal plasticity is only found in a correlational analysis (whereby the shorter the period of visual recovery, the higher the visual cortical responses to auditory stimulation; present study) and in multisensory conditions involving concurrent visual stimulation (Guerreiro et al, 2015). These results resemble those obtained in the domain of auditory restoration but after late-onset deafness: although crossmodal plasticity after cochlear implantation in deaf individuals is often reported (Doucet et al, 2006;Buckley and Tobey, 2011;Sandmann et al, 2012;Stropahl et al, 2015), a recent longitudinal study found that crossmodal visual responses within auditory areas decrease after auditory restoration, eventually reaching the level observed in normally hearing controls (Rouger et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…In addition, cross-modal reorganization may occur, with mainly higher order auditory structures being recruited by other sensory modalities such as vision (Kral, 2007). This phenomenon is illustrated by Buckley & Tobey (2011), who showed that higher activation in the auditory cortex in response to peripheral visual movements was correlated with lower speech understanding scores in CI users with a prelingual onset of deafness. In conclusion, differences in auditory processing may explain the reduced speech understanding performance as compared to post-lingually deafened CI-users.…”
Section: Introductionmentioning
confidence: 75%
“…Some studies have reported negative interference from visual inputs for auditory processing in deaf subjects (Doucet et al, 2006;Buckley and Tobey, 2011;Sandmann et al, 2012;Chen et al, 2016). Conversely, beneficial cross-modal effects for speech understanding have been reported, mainly in the postlingually deaf (Giraud et al, 2000;Rouger et al, 2007;Stropahl et al, 2015).…”
Section: Auditory Activation Of the Secondary Auditory Cortex In Deafmentioning
confidence: 99%